Pendampingan Pelatihan Etika Bisnis Islam Pada Anggota Koperasi Bhara Wiratama Surabaya Dalam Menjalankan Kegiatan UMKM - Kholishudin, Kholishudin; Rikantasari, Shelvyna (Journal of Community Engagement in Economics, 2023)
Micro, Small and Medium Enterprises (MSMEs) in Indonesia are one of the solutions inovercoming economic problems. Surabaya is the second largest city in Indonesia after Jakarta,where many residents are MSMEs under the auspices of the Bhara WIratama Cooperative. Theaim of this service is to provide understanding to MSMEs regarding business ethics in Islam. Itis hoped that MSMEs can benefit from this Islamic business ethics training. The method used inthis service consists of several stages, namely surveys, training and mentoring. The first stage isa survey conducted on the chairman of the Bhara Wiratama cooperative, then the second stageis the implementation of training attended by MSME participants under the auspices of the BharaWiratama Cooperative, and the last is the mentoring stage, namely the service team goes to theMSME location to see the implementation of Islamic business ethics in His business is in makingtransactions, choosing quality materials and developing his business in order to get blessingsfrom Allah SWT.